2009
DOI: 10.1074/jbc.m109.054254
|View full text |Cite
|
Sign up to set email alerts
|

Syndecan-2 Functions as a Docking Receptor for Pro-matrix Metalloproteinase-7 in Human Colon Cancer Cells

Abstract: Although elevated syndecan-2 expression is known to be crucial for the tumorigenic activity in colon carcinoma cells, how syndecan-2 regulates colon cancer is unclear. In human colon adenocarcinoma tissue samples, we found that both mRNA and protein expression of syndecan-2 were increased, compared with the neighboring normal epithelium, suggesting that syndecan-2 plays functional roles in human colon cancer cells. Consistent with this notion, syndecan-2-overexpressing HT-29 colon adenocarcinoma cells showed e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
61
0
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
3

Relationship

3
7

Authors

Journals

citations
Cited by 70 publications
(69 citation statements)
references
References 34 publications
6
61
0
2
Order By: Relevance
“…This finding is supported by the observed absence of (N-terminal) Shh processing in heparan sulfate-deficient cells and the potentiation of Shh processing by exogenous heparan sulfate in vitro. Hh sheddase activation by heparan sulfate is further consistent with the known increase of Hh solubilization by Suramine, a polysulfated compound (Etheridge et al, 2010) and with Syndecan 2 (another cell surface HSPG) acting as a docking receptor and activator for MMP7 (Ryu et al, 2009). Moreover, ADAM12 associates with HSPGs through its cysteine-rich domain (Iba et al, 2000), and heparan sulfate binding to ADAM12 transiently activates the enzyme (Sorensen et al, 2008).…”
Section: Discussionsupporting
confidence: 54%
“…This finding is supported by the observed absence of (N-terminal) Shh processing in heparan sulfate-deficient cells and the potentiation of Shh processing by exogenous heparan sulfate in vitro. Hh sheddase activation by heparan sulfate is further consistent with the known increase of Hh solubilization by Suramine, a polysulfated compound (Etheridge et al, 2010) and with Syndecan 2 (another cell surface HSPG) acting as a docking receptor and activator for MMP7 (Ryu et al, 2009). Moreover, ADAM12 associates with HSPGs through its cysteine-rich domain (Iba et al, 2000), and heparan sulfate binding to ADAM12 transiently activates the enzyme (Sorensen et al, 2008).…”
Section: Discussionsupporting
confidence: 54%
“…Transient transfections were carried out using Vivamagic (Vivagen, Seongnam, Korea), as described in the provided protocol. Monoclonal (mAb) antibody to syndecan-2 (SDC2) was produced by AdipoGen (Incheon, Korea) (19).…”
Section: Methodsmentioning
confidence: 99%
“…A recent study reported that syndecan-4 functions in an FGF2-independent manner, further showing that the GAG chains attached to the syndecan-4 core protein are not required for syndecan-4 effects on turkey satellite cell proliferation or initial differentiation (Zhang et al, 2008), although the nature of possible extracellular ligands is unclear. The syndecan-2 core protein appears to directly bind the pro form of matrix metalloproteases-7 (MMP-7) independent of GAG chains (Ryu et al, 2009), and the physiological anti-elastase, α1-antitrypsin, binds to the deglycosylated syndecan-1 core protein but not to glycosylated syndecan-1 (Chan et al, 2009). Recent evidence suggests that the core protein of syndecan-1 can directly interact with β3 integrin (Beauvais et al, 2009).…”
Section: Cooperativity Of Core Protein and Gag Chainsmentioning
confidence: 99%